UNDANG-UNDANG JINAYAT SYARIAT ISLAM DI ACEH ANTARA IMPLEMENTASI, ISU DAN TANTANGAN - Hudzaifah Achmad Qotadah; Adang Darmawan Achmad (Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2020)
Qanun Jinayat is a criminal law unit that applies to the people of Aceh which is formed based on Islamic sharia values. This study aims to answer the suitability of the Aceh Qanun position with the statutory system, both in terms of implementation, issues and challenges in its implementation. This research uses the juridical normative method with references to Law Number 18 of 2001 concerning Special Autonomy, Law Number 11 of 2006 concerning Aceh Governance, and Qanun Number 6 of 2014 concerning the Law of the Law. The results of this study conclude that the Qanun Jinayat currently enforced in Aceh in its implementation there are challenges from both pro and contra communities, besides that there is also a growing issue that the application of Qanun Jinayat is contrary to the principles of statutory regulations and human rights.